RANCANG BANGUN SISTEM PENJERNIHAN DAN DEKONTAMINASI AIR SUNGAI BERBASIS BIOSAND FILTER DAN LAMPU ULTRAVIOLET - Endarko, Endarko; Putro, Triswantoro; Nuzula, Nike Iza; Armawati, Nuning; Wardana, Adi; Rubiyanto, Agus; Muntini, Melania S (BERKALA FISIKA, 2013)
Design and fabrication of appropriate technology (biosand filter) that is directly can beapplied for community has successfully been carried out for providing clean water. Thetechnology is adopted from slow sand filter method. Biosand filter that has been fabricated whichÂ is technology that is able to filter river water become clean water through filtration process fromÂ sand, gravel and an active carbon. For getting drinkable water from river water, biosand filter hasbeen combined with reverse osmosis system and ultraviolet disinfection. System of reverse osmosisand ultraviolet disinfection are used to reduce any bacteria, virus and total dissolved solids (TDS)from treated water which is resulted from biosand filter process. The results from Balai BesarLaboratorium Kesehatan Surabaya (BBLKS) has been declared that treated water from biosandfilter is met the test standards chemical and physical according to the regulation. Meanwhile theprocessed water from process through biosand filter, reverse osmosis and ultraviolet disinfectionis got predicate as drinkable water with met the test standards microbiological, chemical andphysical.Keywords: biosand filter, reverse osmosis, ultraviolet, drinking water